Influence of potassium and sodium nutrition on leaf area components in Eucalyptus grandis trees - Battie-Laclau, Patricia; Laclau, Jean-Paul [UNESP]; Piccolo, Marisa de Cassia; Arenque, Bruna Cersózimo; Beri, Constance; Mietton, Lauriane; Muniz, Marta R. Almeida; Jordan-Meille, Lionel; Buckeridge, Marcos Silveira; Nouvellon, Yann; Ranger, Jacques; Bouillet, Jean-Pierre (Springer Nature, 2013)
Background and Aims: Recent studies showed a positive tree response to Na addition in K-depleted tropical soils. Our study aimed to gain insight into the effects of K and Na fertilizations on leaf area components for a widely planted tree species. Methods: Leaf expansion rates, as well as nutrient, polyol and soluble sugar concentrations, were measured from emergence to abscission of tagged leaves in 1-year-old Eucalyptus grandis plantations. Leaf cell size and water status parameters were compared 1 and 2 months after leaf emergence in plots with KCl application (+K), NaCl application (+Na) and control plots (C). Results: K and Na applications enhanced tree leaf area by increasing both leaf longevity and the mean area of individual leaves. Higher cell turgor in treatments +K and +Na than in the C treatment resulting from higher concentrations of osmotica contributed to increasing both palisade cell diameters and the size of fully expanded leaves. Conclusions: Intermediate total tree leaf area in treatment +Na compared to treatments C and +K might result from the capacity of Na to substitute K in osmoregulatory functions, whereas it seemed unable to accomplish other important K functions that contribute to delaying leaf senescence. © 2013 Springer Science+Business Media Dordrecht.
Keywords: Cell size; Cell turgor; Expansion; K; Leaf area; Leaf lifespan; Leaf longevity; Na; Nutrient; Osmotic potential; Soluble sugars